2008
DOI: 10.1007/s10396-007-0168-5
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal screening for circumvallate placenta

Abstract: The current results suggest that measurement of placental thickness is useful for screening for circumvallate placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…SGA and CLD incidences were higher in the circumvallate placenta group than in controls. As to the association between circumvallate placenta and SGA, fetal growth restriction has been speculated to be caused by placental insufficiency due to a marginal infarct, hemorrhage, and hemosiderin deposition, in addition to a hypoplastic placenta [ 2 , 11 ]. It has also been suggested that prolonged vaginal bleeding during pregnancy causes hemosiderin deposition in the placenta and chorion, resulting in diffuse chorioamniotic hemosiderosis, and that the fetus may swallow bloody amniotic fluid and thereby develop CLD [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SGA and CLD incidences were higher in the circumvallate placenta group than in controls. As to the association between circumvallate placenta and SGA, fetal growth restriction has been speculated to be caused by placental insufficiency due to a marginal infarct, hemorrhage, and hemosiderin deposition, in addition to a hypoplastic placenta [ 2 , 11 ]. It has also been suggested that prolonged vaginal bleeding during pregnancy causes hemosiderin deposition in the placenta and chorion, resulting in diffuse chorioamniotic hemosiderosis, and that the fetus may swallow bloody amniotic fluid and thereby develop CLD [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bey et al [ 14 ] say that when vaginal bleeding occurs in the 2nd trimester despite a normally implanted placenta, circumvallate placenta should be included in the differential diagnosis. Several studies have reported that circumvallate placenta can be diagnosed based on ultrasonographic abnormalities in placental appearance [ 2 5 , 15 ]. McCarthy et al [ 5 ] reported diagnostic criteria based on an irregular, uplifted placental edge (rounded placental margin) or a marginal shelf or rim (thin or sheet-like placental edge).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On examination, there is a characteristic white ring around the surface of the placental disk that is comprised of a double layer of amnion and chorion with fibrin and necrotic villi. It is predisposed to abnormal separation and commonly presents with 2nd trimester vaginal bleeding, being diagnosed via ultrasound or after delivery [23]. Pregnancy complications are common and include oligohydramnios, small for gestational age (SGA) neonates, abruption, and intrauterine fetal demise (IUFD) [24][25][26].…”
Section: Dmentioning
confidence: 99%